2016
DOI: 10.1158/1078-0432.ccr-15-1965
|View full text |Cite
|
Sign up to set email alerts
|

Disruption ofin vivoChronic Lymphocytic Leukemia Tumor–Microenvironment Interactions by Ibrutinib – Findings from an Investigator-Initiated Phase II Study

Abstract: Purpose Chronic lymphocytic leukemia (CLL) cells depend on microenvironmental interactions for proliferation and survival that are at least partially mediated through B cell receptor (BCR) signaling. Ibrutinib, a Bruton’s tyrosine kinase inhibitor, disrupts BCR signaling and leads to the egress of tumor cells from the microenvironment. While the on-target effects on CLL cells are well defined, the impact on the microenvironment is less well studied. We therefore sought to characterize the in vivo effects of ib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
212
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(234 citation statements)
references
References 50 publications
16
212
2
4
Order By: Relevance
“…Niemann et al reported decreased T-cell activation, proliferation, and PD-1 expression in patients with CLL after ibrutinib therapy. 84 Consistent with prior findings in ITK knockout mice, the authors demonstrated reduced proliferation of circulating Th17 cells in these patients and inhibition of Th17 differentiation in ex vivo assays. In addition, ibrutinib treatment disrupted CLL-macrophage interactions in bone marrow specimens.…”
Section: Ibrutinib In T Cells and Other Immune Cellssupporting
confidence: 84%
“…Niemann et al reported decreased T-cell activation, proliferation, and PD-1 expression in patients with CLL after ibrutinib therapy. 84 Consistent with prior findings in ITK knockout mice, the authors demonstrated reduced proliferation of circulating Th17 cells in these patients and inhibition of Th17 differentiation in ex vivo assays. In addition, ibrutinib treatment disrupted CLL-macrophage interactions in bone marrow specimens.…”
Section: Ibrutinib In T Cells and Other Immune Cellssupporting
confidence: 84%
“…However, recent data demonstrate ibrutinib induces significant suppression of inflammatory cytokines (i.e. TNFα, IL2RA and CXCL13), as well as a downregulatory effect on T-cells and macrophages [9][10][11][12]. It is possible that re-activation of both tumoral and microenvironmental cells during an ibrutinib hold could generate a cytokine release syndrome and cause the withdrawal symptoms reported here.…”
mentioning
confidence: 71%
“…Ibrutinib is the first in a class of US Food and Drug Administration (FDA)-approved Bruton tyrosine kinase inhibitor that acts by blocking B-cell antigen receptor signaling and changing the tumor microenvironment, 6 thereby reducing malignant proliferation of B cells and inducing apoptosis. [6][7][8] It is indicated in relapsed/refractory and in treatment-naïve 17p-deleted CLL.…”
mentioning
confidence: 99%